Three times lucky - Turnage, Sheila (New York : Puffin Books, 2012)
Washed ashore as a baby in tiny Tupelo Landing, North Carolina, Mo LoBeau, now eleven, and her best friend Dale turn detective when the amnesiac Colonel, owner of a café and co-parent of Mo with his cook, Miss Lana, seems implicated in a murder.
Keywords: Mystery and detective stories; Restaurants -- Fiction; Community life -- North Carolina -- Fiction; Identity -- Fiction; Murder -- Fiction; Foundlings -- Fiction; North Carolina -- Fiction